2020
DOI: 10.3390/electronics10010017
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Deep Learning Architectures for Supervised Speech Enhancement

Abstract: Recent speech enhancement research has shown that deep learning techniques are very effective in removing background noise. Many deep neural networks are being proposed, showing promising results for improving overall speech perception. The Deep Multilayer Perceptron, Convolutional Neural Networks, and the Denoising Autoencoder are well-established architectures for speech enhancement; however, choosing between different deep learning models has been mainly empirical. Consequently, a comparative analysis is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 107 publications
0
25
0
Order By: Relevance
“…In recent years, the development of deep learning technology has substantially improved the performance of speech processing algorithms such as automatic speech recognition (ASR) [ 1 , 2 ], speech separation [ 3 ], and speech enhancement [ 4 ]. Among them, ASR has been popularly deployed for voice-enabled information retrieval using artificial intelligence (AI) speakers and chatbots [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the development of deep learning technology has substantially improved the performance of speech processing algorithms such as automatic speech recognition (ASR) [ 1 , 2 ], speech separation [ 3 ], and speech enhancement [ 4 ]. Among them, ASR has been popularly deployed for voice-enabled information retrieval using artificial intelligence (AI) speakers and chatbots [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, speech enhancement techniques have been developed to enhance speech quality for voice communications equipped with a single-channel microphone or a multi-channel microphone array [ 4 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. To overcome the noise robustness of ASR, the developed speech enhancement algorithm can be used as a front-end of ASR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data-driven approach (Zhao et al 2018) of the deep neural network makes it more efficient and is responsive to untrained conditions and unseen noises. In the recent past, the commonly used techniques for supervised speech enhancement (Nossier et al 2021) technique include the mapping in the frequency domain or time-frequency masking. The speech signal is converted from the frequency domain to the time domain.…”
Section: Introductionmentioning
confidence: 99%
“…Nossier et al [20] have demonstrated a comparative analysis on the basis of three classes including the initially proposed Deep Multi-layer Perceptron (MLP), Convolutional Neural Networks (CNN), and Denoising Autoencoder (DAE). The work carried out investigates the impact of network hyperparameter changes and data arrangement on the performance together with the Lombard effect.…”
Section: Introductionmentioning
confidence: 99%